The Research PRoductivity of the Allama Iqbal Open University,Pakistan: A Bibliometric Appraisal - Ikram Ul Haq (IJoLIS, 2024)
Purpose: The study aimed to explore the publication output and research tendencies of Allama Iqbal Open University (AIOU),Pakistan from 1989 to 2020 as reflected in the Scope database.